PENGARUH ROLE PLAYING TERHADAP LITERASI NUMERASI MATERI PERKALIAN PESERTA DIDIK KELAS III SD - Ardiwanata, Moh.; Lestari, Wahyu Maulida (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2025)
This study aimed to investigate the effect of the Role Playing learning model on the numeracy literacy skills of third-grade students at SDN Karangtanjung in multiplication material. The background of this research lies in the low numeracy literacy skills of students, as indicated by the average scores falling below the Minimum Mastery Criteria (KKM). The research employed an experimental method with a One Group Pretest-Posttest design involving 30 students as the sample. The instrument consisted of a descriptive test comprising 10 items that had been validated for both validity and reliability, and was administered before and after the implementation of the learning model. Data were analyzed using a normality test and a Paired Sample t-Test. The results showed that the average pretest score of 26.23 increased to 64.07 on the posttest, with a significance value (Sig. 2-tailed) of 0.000 < 0.05. Accordingly, the Role Playing learning model has been proven to have a significant impact on improving students' numeracy literacy skills in multiplication material. This learning model offers an active and contextual learning experience, enabling students to more easily understand multiplication concepts and apply them in real-life situations. In conclusion, the Role Playing model is effective in enhancing numeracy literacy skills in multiplication and can serve as an innovative alternative instructional strategy in elementary education. This study opens opportunities for further development, both in exploring other variables and in applying the model to other subjects, supported by adequate teacher training. ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran Role Playing terhadap kemampuan literasi numerasi peserta didik kelas III SDN Karangtanjung pada materi perkalian. Latar belakang penelitian ini adalah rendahnya kemampuan literasi numerasi siswa yang terlihat dari nilai rata-rata di bawah Kriteria Ketuntasan Minimal (KKM). Penelitian menggunakan metode eksperimen dengan desain One Group Pretest-Posttest yang melibatkan 30 peserta didik sebagai sampel. Instrumen berupa tes uraian 10 butir soal yang telah diuji validitas dan reliabilitasnya, kemudian diberikan sebelum dan sesudah penerapan model pembelajaran. Data dianalisis dengan uji normalitas dan Paired Sample t-Test. Hal ini ditunjukkan dari rata-rata skor pretest sebesar 26,23 yang meningkat menjadi 64,07 pada posttest, serta nilai signifikansi (Sig. 2-tailed) sebesar 0,000 < 0,05. Dengan demikian, model Role Playing memberikan pengaruh yang signifikan terhadap peningkatan kemampuan literasi numerasi siswa pada materi perkalian. Model pembelajaran ini memberikan pengalaman belajar yang aktif dan kontekstual, sehingga siswa lebih mudah memahami konsep perkalian dan menerapkannya dalam kehidupan sehari-hari. Kesimpulannya, model Role Playing efektif meningkatkan kemampuan literasi numerasi pada materi perkalian dan dapat menjadi alternatif strategi pembelajaran yang inovatif di sekolah dasar. Penelitian ini membuka peluang pengembangan lebih lanjut, baik pada variabel lain maupun penerapan di mata pelajaran lain, dengan dukungan pelatihan guru yang memadai.